Effects of psychosocial determinants of health at work on well-being over time: a systematic review of the literature with narrative synthesis - Neto, Mariana (2017)
The temporal question is central to the research on the psychosocial determinants, because of the possibility of studying and deepening the dynamics of this complex web of interactions, which is only possible through longitudinal studies and the use of sophisticated statistical analyses. In order to update the existing information on this field of research using an epidemiological approach, scientific information on the effects of the psychosocial determinants associated with work on the health and Well-being of workers over time was collected and systematized Searches were performed to the databases Medline via PubMed, Embase, PsycInfo, Google Scholar and journals publishing in this area according selection criteria. The selection was performed by two of the authors independently Seven longitudinal studies were identified that met the inclusion criteria and more than 50% of previously defined quality criteria.A narrative synthesis was performed because the studies selected were very heterogeneous regarding the sample size, the observation period, the spacing of the observation moments, the total observation period and the methods of statistical analysis, among others High values of job demands were consistently associated over time with the decrease in well-being and that the control varied inversely with the well-being, but not in a significant way. High supervisor support was associated with high well-being in only three of the four studies that analysed this dimension, but co-workers support only revealed a significant and positive association with well-being in one of two studies. The dimensions of the Work-Family Conflict (Strain-Based Conflict and Time-Based Conflict) had direct effects on the simultaneous analyzes but in one of the studies the cross-lagged effects showed a paradoxical effect in which, being associated with negative effects on the well-being in the concomitant analysis, were associated with an increase in well-being 6 months later in the cross-lagged analysis, which the authors attributed to recovery effects. The work-family facilitation did not reveal any association with well-being over time